Stock of Nuts/Bolts System With A Load Cell Sensor of Digital Scale As An Iot-Based - Khamdi, Nur; Rahmadi Arrahman; Amnur Akhyan (Jurusan Teknik Elektro Universitas Andalas, 2024)
The passage highlights the importance of having a reliable supply of nuts and bolts for Micro, Small, and Medium Enterprises (MSMEs) involved in the manufacturing of appropriate technology tools. Nuts and bolts are critical components in the production process of such manufacturing. Therefore, it is essential to ensure their constant availability to avoid interruptions in the workflow. Currently, many MSMEs still monitor their stock levels manually. This manual method has its drawbacks, as stock levels can sometimes go unnoticed, leading to stockouts when the components are needed. When stock runs out unexpectedly, it can cause delays, as additional time is required to purchase more supplies from wholesalers. In this study, a digital scale with a load cell sensor was developed as a medium for taking inventory or stocking bolts and nuts. This device features several buttons: a button for selecting the size of bolts or nuts, a button for choosing between stocking or taking items, and a button for displaying stock information of bolts or nuts in the warehouse. The results from this digital scale are sent to a website using the Internet of Things (IoT) system as a communication medium between the digital scale and the monitoring website. The results of this study show that the digital scale has an accuracy of 99.95%, and the accuracy of the counted items or stock is 100%.